Application of Decision-Making Models to Improving the Critical Thinking Ability of High School Students on Biology Materials - Mayarni, Mayarni; Anggraini, Tiara; Amirullah, Gufron; Murwitaningsih, Susanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The purpose of this research was to see the influence of learning and examples of decision making on improving the critical thinking skills of first grade students (X) on material change and environmental conservation inÂ  Bekasi High School. Researchers used the Quasy Experiment method with PrePost Control Group Design. The population in the study were first grade students (X MIPA 3) and (X MIPA 4) with the number of students were 35 and 34 students respectively. The technique for sampling was random cluster sampling. The exploration tool used is a 10-point skill test that integrates with indicators of critical thinking abilities or skills. Based on the results of the study, the average value of critical thinking skills or skills in the experimental group (=59.74) was higher than in the control group (=46.08). T-test (3.82) and t-table (2.97) were obtained when the hypothesis was tested using t-tests with a significance level of 1% and learning models such as decision making on improving the critical thinking skills of first grade students on environmental conservation materials at SMA Negeri Bekasi.